KEEFEKTIFAN METODE MEMORY STORY DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA JEPANG - elian, hasyyati; rosliyah, yuyun; prasetiani, dyah (Universitas Negeri Semarang, 2015)
Memorizing the vocabulary is the important thing in learning Japanese. If the students couldn’t memorize it, it will make the learning process don’t run smoothly. This condition was found in SMAN 15 Semarang. The teacher use picture card to teach vocabulary, but the student still couldn’t remember all the vocabulary well. The memory story method will help students memorizing the vocabulary. The idea is, by making an imaginary story of each word, students will remember the vocabulary for a long time. This research was an experiment study. The purpose of this study is to find the effectiveness of memory story in enhancing the student vocabulary. The sample of the experiment class was 28 students from XII IPS 2, and the control class was 28 students from XII IPS 3. The data gathered by using a post-test. The result of pos-test shows that the average score of experiment class was 84.14, higher 4.71 points than the control class (which is only 79.43). The t-test result, prove that memory story was effective to enhance student’s ability in memorizing the Japanese vocabulary.